Colloidal probe dynamics in gelatin solution during the sol–gel transition - Hong, Wei; Xu, Guozhi; Ou, Xiaogang; Sun, Weixiang; Wang, Tao; Tong, Zhen (Soft matter, 2018)
The dynamics of the colloidal probes in a gelatin solution during the time-dependent sol–gel transition was investigated by multi-particle tracking. The relationship between the relaxation of the medium at the critical gel point and the mean square displacement of the probes was elucidated. Based on this understanding, the critical gel point of gelatin and the corresponding critical exponent n were unambiguously determined by the loss angle criterion and the time-cure superposition. The shift factors of the latter are further used to estimate the time/length-scale evolution of the gelatin during the sol–gel transition. The growth of the medium length scale crossed with the two measuring length scales successively at the pre-gel regime. Coinciding with the length-scale crossovers, the probability density function (PDF) of the probe displacements displayed two transient peaks of non-Gaussianity. In the post-gel regime, the third peak of Gaussianity suggested inhomogeneity in the gel network. The non-Gaussianity results from the bifurcation of diffusivity. The present work showed that the non-Gaussian dynamics of the probes are not the direct equivalence of that of the medium, but an effect of length-scale coupling.